Inclusion of men in health services and educational activities: the fathers' perceptions - Melissa Guterres Costa; Adriane Maria Netto de Oliveira; Bárbara Tarouco da Silva; Fabiane Ferreira Francioni; Sandra Beatris Diniz Ebling; Vanessa Franco de Carvalho; Simoní Saraiva Bordignon (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To learn about the perception of fathers regarding their inclusion in health services and/or educational activities. Method: Qualitative, exploratory, and descriptive study addressing 22 fathers participating in a group of pregnant women in Rio Grande, RS, Brazil. Data were collected through semi-structured interviews and analyzed using the content analysis technique. Results: The following categories emerged from the participants' reports: fathers' perceptions regarding their presence in health services and fathers' perceptions regarding their participation in the group of pregnant women. Additionally, they provided contributions and suggestions regarding their experiences with the group's meetings. Conclusion: The participants felt excluded from the services, which shows that health intervention strategies need to be (re)constructed to implement actions that include fathers as active participants in care, so they recognize the importance of their role in healthy human development.